The Effect of Profitability, Firm Size, and Leverage on Islamic Social Reporting with Sharia Supervisory Board as Moderating Variable - Maulana Achmad Chamim; Dita Andraeny (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the effect of profitability, company size, and leverage on the disclosure of Islamic Social Reporting (ISR), this study also analyzes the role of the Sharia Supervisory Board (SSB) as a moderating variable. The role of SSB is very important in the operation of Islamic banks. SSB must be involved in the Company’s decision making, including in the disclosure of ISR. The study was conducted on 11 Islamic Commercial Banks in Indonesia for the period 2020-2023 with a total of 44 samples. The analysis method used in this research is Moderated Regression Analysis (MRA), which is then measured using the eviews 13 test tool. The results showed that Profitability and Company Size had a coefficient value of 0.703009 and 0.022053 and has a positive niali, while Leverage has no effect on ISR and SSB has a significant effect on ISR disclosure, Profitability after being moderated by SSB has no effect on ISR while Company Size and Leverage are strengthened by SSB and have a significant effect on ISR. which means that SSB involvement in making Islamic bank decisions will have a positive impact on Islamic bank activities. Islamic banks will tend to have a high level of ISR.